THE EFFECTIVENESS OF ALLOCATED VILLAGE FUNDS MANAGEMENT (A Study in Pelalawan District, Riau Province, Indonesia) - Savitri, Enni; Gumanti, Tatang Ary; Andreas, Andreas; Diyanto, Volta (Jurnal Aplikasi Manajemen, 2018)
This study aimed to analyze the effectiveness of the management ofAllocated Village Funds (AVF) through the stages of planning, implementing, reporting, and the accountability and to see if it was completed in a transparent and accountable manner. Each stage of the management process has the rules that must be understood and implemented according to the Ministry of Home Affairs RegulationNo. 113 year 2014. Accountability of village funds is required to be managed transparently, accountable and participative. This research used a qualitative method. Primary data were obtained through interviews with 28 informants. Research informants were village heads, village secretaries and village treasurers. Research locations were 104 villages in 12 subdistricts in the Pelalawan District, Riau Province. The method of data collection was through interview, observation, and documentation. To validate the data the triangulation method was used. The results showed that the system of management for the AVF was in accordance with the provisions of the legislation. However, in the implementation of AVF, some obstacles were found such as the quality of human resources in operating the management system, limitations in the availability of supporting equipment in the village offices to facilitate the process of AVF's, and the lack of facilities and infrastructure at the village offices. Also, it was found that the village management team needed to receive some training to improve their knowledge and expertise in carrying out the management of AVF.